LINGUOCULTURAL FEATURES OF PROVERBS AND SAYINGS ABOUT SCIENCE IN ENGLISH AND UZBEK (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The heritage of any nation is rich not only in its tangible achievements, but also in its intangible assets, among which proverbs and sayings have a paramount place. These concise and figurative expressions, having been formed over centuries, reflect the collective worldview, values, traditions, and beliefs of a society. In both English and Uzbek cultures, proverbs and sayings related to science, learning, and knowledge constitute an essential part of the linguistic and cultural heritage. They represent the appreciation of the importance of science and learning, and manifest the ways in which both societies perceive intellectual pursuit, the value of education, and the status of the learned individual.